Predictors of fast visual recovery in idiopathic intracranial hypertension: a cohort study - Storarri, Ana Carolina Montouro; Lee, Annelise Akemi Higa; Gonzaga, Bruno Pissolati Mattos; Sawada, Luis Armando; Santos, Beatriz Marques dos; Arthuzo, Lorrane Campidelli; Marques , Thassia Cavalcante de Oliveira Moraes; Domingues, Renan Barros (Headache Medicine, 2024)
Introduction Idiopathic intracranial hypertension (IIH) is characterized by increased intracranial pressure without a discernible cause, often leading to visual impairment and papilledema. Understanding the factors influencing visual outcomes in IIH patients is crucial for improving management strategies. This study aimed to identify predictors of satisfactory visual outcome (SATISF) defined as the resolution of reduced visual acuity and/or disappearance of papilledema. Objective To evaluate the factors associated with satisfactory visual outcomes in female patients with IIH. Methods This retrospective cohort study included female patients diagnosed with IIH. The potential predictors of a satisfactory visual outcome evaluated were age, initial body mass index (BMI), cerebrospinal fluid (CSF) opening pressure (Pi), duration of symptoms, and the need to discontinue acetazolamide. Visual outcomes were categorized as SATISF or non-satisfactory (NAOSATISF). Independent sample t-tests were used for comparing means, and chi-square tests were employed for comparing proportions. The average interval between the first and second visual assessments was 55.4±48.4 days. Results The study involved the following comparative results: Age: NAOSATISF 32.2±12 years, SATISF 35.9±18.8 years, P=0.3 BMI: NAOSATISF 33.4±4.3, SATISF 33.7±4.3, P=0.8 Pi: NAOSATISF 41.7±12.5 cmH2O, SATISF 39.3±13.2 cmH2O, P=0.5 Duration of symptoms: NAOSATISF 352.25±566.5 days, SATISF 317.2±815.7 days, P=0.9 Acetazolamide discontinuation: NAOSATISF 4.7%, SATISF 15.7%, P=0.24 None of the evaluated factors showed a statistically significant association with satisfactory visual outcomes. Conclusion This study did not identify any significant predictors of satisfactory visual outcomes in IIH patients. The results suggest that age, BMI, CSF opening pressure, duration of symptoms, and the need for acetazolamide discontinuation do not significantly impact visual recovery. Further research is needed to better understand the factors contributing to the rapid neuro-ophthalmological recovery in IIH patients.